A Phase 2, Multi-Center, Randomized, Double-Blind, Parallel-Group Trial to Evaluate the Efficacy and Safety of CKD-495 in Patients With Acute and Chronic Gastritis - Su Hyun Park; Oh Young Lee; Yong Chan Lee; Kyung Sik Park; Jong Jae Park; Moo In Park; Geun Am Song; Dong Ho Lee; Hyunsoo Jung; Sung Kook Kim; Tae Nyeun Kim; Suck-Chei Choi; et al. (Canadian Journal of Gastroenterology and Hepatology)
Trial Registration: ClinicalTrials.gov identifier: NCT03437785